Characterization of the Murine SIRT3 Mitochondrial Localization Sequence and Comparison of Mitochondrial Enrichment and Deacetylase Activity of Long and Short SIRT3 Isoforms - Bao, Jianjun (2010)
SIRT3 is identified as the major mitochondrial deacetylase. Two distinct isoforms of the murine SIRT3 have been identified with the short isoform having no recognizable mitochondrial localization sequence (MLS) and the long isoform having a putative MLS. A recent study questions the mitochondrial deacetylase activity of this short isoform. In contrast, the long isoform has been shown to be predominantly mitochondrial with robust deacetylase activity. Here we investigate whether the amino-terminus of the long SIRT3 isoform is a legitimate MLS and evaluate in-situ mitochondrial deacetylase activity of both isoforms. We confirm the presence of long and short isoforms in murine liver and kidney. The long isoform is generated via intra-exon splicing creating a frame-shift to expose a novel upstream translation start site. Mitochondrial localization is significantly more robust following transfection of the long compared to the short isoform. Insertion of this alternatively spliced novel 5’ sequence upstream of a GFP-reporter plasmid shows greater than 80% enrichment in mitochondria, confirming this region as a legitimate mitochondrial localization sequence. Despite lower mitochondrial expression of the short isoform, the capacity to deacetylate mitochondrial proteins and to restore mitochondrial respiration is equally robust following transient transfection of either isoform into SIRT3 knockout embryonic fibroblasts. How these alternative transcripts are regulated and whether they modulate distinct targets is unknown. Furthermore, in contrast to exclusive mitochondrial enrichment of endogenous SIRT3, overexpression of both isoforms show nuclear localization. This overexpression effect, may partially account for previously observed divergent phenotypes attributed to SIRT3.